PENGEMBANGAN EVALUASI BERBASIS DIGITAL MELALUI WEB WORDWALL PADA PESERTA DIDIK KELAS V SEKOLAH DASAR - Ida Muza Kirotul Umah; Indhira Asih Vivi Yandari; Zerry Rahman Hakim (STKIP Persada Khatulistiwa Sintang, 2023)
This research aims to determine the feasibility and response of students to evaluation of digital-based learning via web wordwall for class V students. The research method used is Research and Development (R&D) based on the Borg and Gall development design which has been modified into six stages, namely : analysis of potential and problems; data collection; product design; design validation; design revision; and test use. Based on the results of the analysis, media experts gave an average score of 84%, material experts gave an average score of 86% and language experts gave an average score of 81%. The average score obtained by all experts was 83.83% when interpreted as falling within the very appropriate criteria. Furthermore, supported by the calculation of the response questionnaire, students who carried out the evaluation obtained 96% results in the very good category. Thus, it can be concluded that the digital-based learning evaluation development product via the wordwall web is very feasible and very good to use as an evaluation tool in assisting the learning activities of fifth grade elementary school students.